2020
DOI: 10.1002/mgg3.1249
|View full text |Cite
|
Sign up to set email alerts
|

Candidate gene associations reveal sex‐specific Graves’ disease risk alleles among Chinese Han populations

Abstract: BackgroundWith several susceptibility single nucleotide polymorphisms identified by case–control association studies, Graves’ disease is one of the most common forms of autoimmune thyroid disease. In this study, we aimed to determine whether any observed differences in genetic associations are influenced by sex in Chinese Han populations.MethodsA total of 8,835 patients with Graves’ disease and 9,936 sex‐matched healthy controls were enrolled in the study. Confirmed by a two‐staged association analysis, sex‐sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Graves’ disease is an autoimmune disease that affects the thyroid gland, where deregulated thyroid function is caused by autoantibodies generated to the thyrotropin receptor. , In humans, this autoimmune disease can occur at all ages but seems to mostly affect women in a reproductive age group . Initial GWAS studies on populations prone to this autoimmune condition suggested that the lyso-PS receptor, GPR174, was among the major risk factors that might lead to Graves’ disease. , Since these initial findings, several focused genomic studies on human subjects suffering from Graves’ disease across the world have identified polymorphisms or mutations to GPR174 to be the causative factor for the pathology and progression of the dysregulated thyroid function associated with this autoimmune disease. Along similar lines, Addison’s disease (also known as Adrenal Insufficiency) is another autoimmune condition marked by an inability of the adrenal gland to produce hormones (particularly cortisol). , Genomic studies on populations suffering from Addison’s disease suggest that polymorphisms to GPR174 might also have a causal role in the pathogenesis of this autoimmune disease. …”
Section: Diseases Associated With Dysregulated Lyso-ps Metabolism or ...mentioning
confidence: 99%
“…Graves’ disease is an autoimmune disease that affects the thyroid gland, where deregulated thyroid function is caused by autoantibodies generated to the thyrotropin receptor. , In humans, this autoimmune disease can occur at all ages but seems to mostly affect women in a reproductive age group . Initial GWAS studies on populations prone to this autoimmune condition suggested that the lyso-PS receptor, GPR174, was among the major risk factors that might lead to Graves’ disease. , Since these initial findings, several focused genomic studies on human subjects suffering from Graves’ disease across the world have identified polymorphisms or mutations to GPR174 to be the causative factor for the pathology and progression of the dysregulated thyroid function associated with this autoimmune disease. Along similar lines, Addison’s disease (also known as Adrenal Insufficiency) is another autoimmune condition marked by an inability of the adrenal gland to produce hormones (particularly cortisol). , Genomic studies on populations suffering from Addison’s disease suggest that polymorphisms to GPR174 might also have a causal role in the pathogenesis of this autoimmune disease. …”
Section: Diseases Associated With Dysregulated Lyso-ps Metabolism or ...mentioning
confidence: 99%